STRATEGI SCRIPT WRITER DALAM PENULISAN NASKAH VIDEO CAMPAIGN PT LIZZIE PARRA KREASI DENGAN TEMA “EARTHDAY WITH BLP” - Hamdi Hasibuan, Ilal; Dharmawan, Leonard (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Earth Day has become a global momentum that encourages various brands to increase their awareness of environmental issues, including the beauty industry, which produces large amounts of cosmetic packaging waste. This study aims to analyze the script writer’s strategy in writing the script for BLP Beauty’s “Earthday with BLP” video campaign, as well as the application of visual symbols in building audience emotional engagement. The study uses a descriptive qualitative method with a content analysis approach toward the video campaign script and observations of the scriptwriting process. The writing of the video campaign script was carried out using the Brand Storytelling method based on Donald Miller’s concept, which includes core message development, character framing, narrative structuring, emotional and visual integration, and call to action. The implementation of these elements in the video campaign script is able to build audience emotional engagement while strengthening the brand’s image as environmentally conscious and relevant to the audience’s daily lives.